The thorn - Lewis, Beverly, 1949- (Minneapolis : Bethany House, 2010)
Rose's older sister, Hen, knows more than she should about falling for the wrong man. Unable to abandon her Amish ways, Hen is soon separated from her very modern husband. Mattie, their young daughter, must visit her father regularly, but Hen demands she wear Amish attire--and speak Pennsylvania Dutch, despite her husband's wishes. Will Hen be able to reestablish her place among the People she abandoned? And will she be able to convince Rose to steer clear of rogue neighbor Nick?
Includes bibliographical references and index.
Keywords: Amish -- Fiction; Sisters -- Fiction; Pennsylvania Dutch Country (Pa.) -- Fiction; Christian fiction